Environmental Problems Of Visual Environment Urbosystems (On The Example Leninsky District Of Kharkiv) - Kоchanov, Е. А.; Kоchanovа, І. Е. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2014)
Environmental problems are usually linked to air and water pollution, with high levels of noise pollution and radiation, but never at the same time mentions the environmental factor as a visual medium and its status. Moreover, it is assumed that all we need - it's pure air, clean water and we do not care about what we look. Visual environment of modern cities in Ukraine affects the health of the inhabitants of these cities. Conducted a study on the state of the visual environment of Leninsky district of Kharkov and made recommendations to improve the visual fields.